Makna Simbol Hau Monef Bagi Masyarakat Timor-Suku Dawan - Amsikan, Hendrikus Rinaldi (Perspektif, 2024)
Time changes, and so do humans. This statement remains relevant today, as people become increasingly aware of the close relationship between time and creativity. Within the framework of social life, this proverb emphasizes that throughout life, the ways individuals express themselves also evolve, which in turn influences their efforts to seek meaning related to themselves, others, nature, and God. This reality illustrates that humans are cultural beings capable of creating culture. In this context, the theme of this paper is "The Meaning of the Hau Monef Symbol for the Timorese Dawan Community." The author has chosen this theme because it seems that the Dawan community, particularly the younger generation, lacks the habit of exploring the meanings behind each symbol in their culture. Thus, this paper aims to assist the Dawan community in understanding the significance of their cultural symbols, especially Hau Monef. The method employed by the author includes a literature review and personal insights, drawing on various sources related to culture to enhance this writing.